A Study on La Genèse du Roman Persan Modern Translated to Persian by M. Ghavimi and N.-D. Khatat - Rohollah Ghasemi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Christophe Balaÿ is one of the iranologists who has sacrificed their whole life to study Persian literature and the outcome is a book, entitled Genèse du roman persan modern, which has been translated to Persian by two Iranian university professors Mahvash Ghavimi and Nasrine-Dokht Khatat. The analysis of this translation and the comparison with the original text written in French can depict us the translators’ positioning facing with different challenges in text. And such a study could be interesting and helpful not only for professional translators but for students who aim to have a take a more profound look on this translation. We used Vinaya and Darbelent’s method because it is one of the most used and useful methods in this domain. In this article, we try to demonstrate which strategies the translators use in order to convey the meanings and to respect the structures of the text. In fact, the principal question we tried to answer to is: why translator chooses some structures and refuses the others? Finally, it is concluded that the product-based translation of this book seeks to attract Persian speakers and make them comprehend the materials as efficiently as possible.